AN URINARY BIOSENSOR FOR EARLY STAGE OVARIAN CANCER DETECTION: EXPERIMENTAL CHARACTERIZATION - (:unkn) unknown (AMER SOC MECHANICAL ENGINEERS, 2013)
In this study, an experimental characterization of a piezoelectric ultrasonic MEMS biosensor for detection of antiapoptotic protein Bcl-2 in sub ng/ml scale is presented. Bel-2 is demonstrated to be elevated at different stages of ovarian cancer in urine ranging from 0.5 to 12 ng/ml. Here, shear horizontal (SH) polarized surface acoustic waves (SAWs) were utilized by interdigital transducers (IDTs), which were micro fabricated on piezoelectric ST cut Quartz wafers. SH SAWs were generated and sensed by a pair of IDTs, separated by judiciously designed a delay path in-between with for most effective Bcl-2 capture. The Bcl-2 concentration is characterized with respect to the change in resonance frequency. The target sensitivity for diagnosis and quantifying the stage of ovarian cancer is achieved with successful detection of Bcl-2 levels as low as 0.5 ng/ml. The results are promising for the sensor system to be used in a lab-on-a-chip platform for point of care urinary ovarian cancer monitoring diagnosis.